Analysis on the Difference of Energy Evolution in the Process of Energy Storage Failure of Strong Coal Rush Rock Samples under Different Adaptive Modification Regulation Measures - Fangfang Zhang (Shock and Vibration)
Current energy to “release” after accumulating + first for the mechanism of rock bursts occurred in analysis of the strategy is accepted by many scholars, based on the existing means of prevention and control of percussive ground pressure, from the angle of the prevention and control of design of the mechanism of impact ground pressure energy regulation, namely, “weakened after the first release +” softened water injection measures and “lead after the first release +” drilling pressure relief measures, for the study of mining under the action of a strong shock tendentiousness rock energy regulatory mechanism; based on rock mechanics experiment, the analysis under different modification measures should be variant energy storage mechanisms of induced damage evolution of rock energy. The mechanism of energy evolution in the modification of strong bursting liability roof rock is revealed. The results show that different modification regulation measures can effectively change the physical and mechanical parameters of target rock samples and realize “hard rock softening or soft rock hardening.” Samples under different modification measures are classified as initial consolidation stage, elastic stage, stage of plastic deformation, yield failure stage, and late stage, the energy evolution is roughly the same as the sample complete natural condition, but the yield failure stage and the destruction of late stage have an obvious difference, which provides favorable conditions for impact ground pressure to prevent. With the help of three characteristic energy indexes of total strain, elastic strain energy, and dissipative strain energy of rock samples, the evolution law of energy indexes under different modification control measures is analyzed. The index of elastic energy consumption ratio is introduced as a precursor feature of rock instability and failure, which indicates the rock impact tendency to a certain extent. The energy regulation mechanisms of “first release+then weakening” water injection softening measures and “first release+then guidance” drilling pressure relief measures are explained theoretically, respectively. However, we should focus on the defects of the corresponding control measures and finally try to make a reasonable combination of different modification measures. Finally, the gradient pressure relief scheme should be considered in order to avoid large stress drop caused by large-scale pressure relief in the region and aggravate the instability of rock mass. The instability of rock mass is further aggravated.